Essential Newborn Care Practices and Determinants among Lactating Mothers of Biratnagar - Chaudhary, Sangeeta; Niraula , Surya Raj; Sah, Ram Bilakshan; Nepal Gurung, Gyanu; Yadav, Gajendra Prasad; Mandal, Punam Kumari (Journal of Biratnagar Nursing Campus, 2025)
Background : Essential Newborn Care is a set of practices that reduces neonatal morbidity and mortality, such as clean cord care, thermal care (keeping the baby warm by wrapping in clean and dry clothes and delaying bathing until 24 hours after birth), and initiating breastfeeding within the first hour of birth. Essential newborn care (ENC) around the time of birth is critical in improving neonatal survival.Methods: A mixed-method, community-based cross-sectional study was conducted among 338 lactating mothers using a simple random sampling method and three focus group discussions (FGD) in which 10 mothers were involved for qualitative data. Data entry was carried out by EpiData version 3.1, and analysis was done by SPSS (Version 16). Binary logistic regression was used to identify predictors. Qualitative data were analyzed by using a thematic framework.Results: This study found 82.1% of mothers had good practices in essential newborn care. Factors such as age, occupation, and income of the respondent and her husband, the timing of the ANC's first visit, type of family, place of delivery, type of house, latrine, and sources of drinking water were significantly associated with the practice. 250 (89.6%) of the respondent those who visited the health centre for more than 4 visit more likely to have practiced ENC, and it is statistically significance having p-value